Lipopolysaccharide (LPS) introduction during growth and development period of rat’s tooth toward the occurrence of enamel hypoplasia - Didin Erma Indahyani; Al-Supartinah Santoso; Totok Utoro; Marsetyawan HNE Soesatyo (Dental Journal (Majalah Kedokteran Gigi), 2007)
The aim of this study is to know the effect of lipopoly saccharide (LPS) induction during growth and development period specifically the occurrence of hypoplasia on tooth enamel. 5 day old male wistar rats divided into two groups. Group 1 (control) under went no treatment. Group 2 (treatment) under went LPS induction every 24 hour for 8 days on buccal fold right maxillary first molar. After 21 days old the rats were sacrificed and the tooth was resected. Hypoplasia Hypo calcification Index (HHI) was used to determine the degree of hypoplasia by clinical examination. Radiograph of maxilla was also taken to analyze the apacities of enamel by using COREL DRAW version 11. The result showed that group under went LPS induction hypoplasia occurred on its molar tooth and more radiolucent than control groups. The conclusion is LPS induction during growth and development period of rats tooth causing enamel hypoplasia.